Innovative Leadership of School Principals in Promoting Digital Transformation in the Learning Process - Sutopo, Langgeng (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to analyze the role of innovative school leadership in encouraging digital transformation in the learning process. The study was conducted through a qualitative method based on Systematic Literature Review (SLR) by searching scientific articles from three main databases: SINTA, Scopus, and Google Scholar. The initial identification process produced 122 articles, then a screening process was carried out based on inclusion criteria for theme suitability, the 2018–2024 range, and the connection with innovative leadership concepts and digital learning transformation. At the final stage, 25 articles were selected that met the criteria for further analysis. Data collection techniques in SLR are carried out through four stages: (1) identification of keywords such as innovative leadership, digital transformation in education, and school leadership; (2) search for articles in selected databases; (3) selection through PRISMA Flow, including elimination of duplication, head-abstract analysis, and content feasibility review; and (4) data extraction based on innovative leadership indicators, digital transformation strategies, and learning technology implementation results. Data analysis was carried out using thematic synthesis techniques, which map patterns, core concepts, and consistent findings between articles to produce a comprehensive understanding of innovative leadership relationships and learning digitization processes. The results of the study show that school principals with innovative leadership characteristics, especially those oriented towards adaptation, collaboration, and teacher capacity development, play a significant role in accelerating the integration of digital technology in schools. Innovative leadership encourages the strategic use of technology, improves the quality of learning planning, and strengthens a collaborative work culture among educators. These findings confirm that innovative school leadership is a key factor in accelerating digital transformation while building an adaptive learning culture oriented towards improving the quality of education.